The prevalence and habit-associated risk factors of gastroesophageal reflux disease among fishermen in Indonesia - Ahmad Fariz Malvi Zamzam Zein; Catur Setiya Sulistiyana; Tissa Octavira Permatasari; Uswatun Khasanah; Tiar Masykuroh Pratamawati; Ismayanti Ismayanti; Dwi Listiany Corneli; Eni Suhaeni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background. This study was aimed to investigate the prevalence and habit-associated risk factors of gastroesophageal reflux disease (GERD) among fishermen.Methods. A cross-sectional study was conducted among 168 adult fishermen in Cirebon Regency, West Java, Indonesia. A self-administered questionnaire was given. The questionnaire consisted of demographic characteristics and validated GERD questionnaire (GERDQ) in Indonesian language. Data were analyzed using descriptive statistics and chi-square test. The study has been approved by the Medical Research Ethic Comiittee.Results. The medan age of the participants was 39.0 (24-86) years old. They were predominanty (60.7%) female. The prevalence of GERD was 22.6%. According to bivariate analysis, there was association between smoking (PR 1.181; 95%CI 1.013-1.377;p 0.041), high-salt intake (PR 2.419;95%CI 1.079-5.424; p 0.029), herb consumption (PR 3.068; 95%CI 1.307-7.200; p 0.008), poor hand hygiene (PR 3.202; 95%ci 1.445-7.095; p 0.003), and non-steroidal anti-inflammatory drug (NSAID) consumption (PR 3.062; 95%CI 1.446-6.488; p 0.00) with GERD. Tea consumption, coffee consumption, and raw vegetable eating were not associated with GERD.Conclusions This population-based study showed that the prevalence of GERD among fishermen in Indonesia is high. Habits associated with GERD in this study were smoking, high-salt intake, herb consumption poor, hand hygiene,